2016
DOI: 10.1016/j.gde.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

RNA as a fundamental component of interphase chromosomes: could repeats prove key?

Abstract: Beginning with the precedent of XIST RNA as a “chromosomal RNA” (cRNA), there is growing interest in the possibility that a diversity of non-coding RNAs may function in chromatin. We review findings which lead us to suggest that RNA is essentially a widespread component of interphase chromosomes. Further, RNA likely contributes to architecture and regulation, with repeat-rich “junk” RNA in euchromatin (ecRNA) promoting a more open chromatin state. Thousands of low-abundance nuclear RNAs have been reported, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 82 publications
3
30
0
Order By: Relevance
“…Some are highly abundant long non-coding RNAs (lncRNA) such as NEAT1 or MALAT1 or other diverse lncRNAs including FIRRE, HOTAIR, XIST etc. In contrast to these defined lncRNAs other studies [14,15] have suggested that a large proportion of nuclear RNAs hybridise to a C0t-1 probe, indicating that they are enriched in transcripts derived from a repetitive fraction of the genome. They also showed that these RNAs are quite stable and are turned over relatively slowly.…”
Section: Hnrnasmentioning
confidence: 90%
See 2 more Smart Citations
“…Some are highly abundant long non-coding RNAs (lncRNA) such as NEAT1 or MALAT1 or other diverse lncRNAs including FIRRE, HOTAIR, XIST etc. In contrast to these defined lncRNAs other studies [14,15] have suggested that a large proportion of nuclear RNAs hybridise to a C0t-1 probe, indicating that they are enriched in transcripts derived from a repetitive fraction of the genome. They also showed that these RNAs are quite stable and are turned over relatively slowly.…”
Section: Hnrnasmentioning
confidence: 90%
“…In contrast to defined lncRNAs, it has been shown that repetitive non-coding RNA species, labelled using C0t-1 DNA as a probe, do not migrate far from their site of synthesis [14,33]. To us this suggests that many RNAs produced in the nucleus, unless they are proactively transported, will stay in the vicinity of the site of transcription, it was then suggested that once structural RNAs are embedded with chromatin/scaffold proteins they might become very stable [15]. Few studies have looked at the fate of spliced out introns, although the Lawrence group reported that spliced out introns drift into the nucleoplasm over time [14].…”
Section: Rna Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear RNA has long been proposed to play a central role in shaping nuclear structure [13][14][15][16][17][18] . Initial experiments performed more than 30 years ago found that global disruption of RNA (using RNase) leads to large scale morphological deficits in the nucleus 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we note that SAF-A and other nuclear matrix proteins, including many reported to associate with XIST RNA, are not restricted to the Xi, but are distributed widely over chromatin. Thus, it is plausible that this repertoire of scaffolding proteins could interact with other nuclear non-coding RNAs to modify chromatin architecture throughout the genome [ 59 , 60 ]. This perspective, together with our interest in ‘junk’ of the genome, led us to explore the possibility that XIST RNA exemplifies a broader paradigm for non-coding RNA function in nuclear organization.…”
Section: Xist Rna and The Debated Concept Of A Complex Non-cmentioning
confidence: 99%